Changes in muscle damage markers in female basketball players - Moreira, A.; Nosaka, K.; Viveiros, L.; Nunes, J. A.; Jamurtas, T.; Aoki, M. S. (Biology of Sport, 2014)
The aim of the present study was to investigate changes in muscle soreness, blood muscle damage markers, muscle strength and agility following an official basketball match. Eleven elite female professional basketball players (27.4 ± 4.8 years, 179.5 ± 5.5 cm, 72.0 ± 7.8 kg) of a team participated in this study. The official match was the seventh match of the season in the first phase of the Brazilian National Female Basketball Championship. Muscle soreness, plasma creatine kinase activity (CK), and myoglobin concentration (Mb) were determined before and after the match (post-match, 24 and 48 hours after the match). The 1RM strength for bench press and leg press, and the agility T test were assessed before and at 24 and 48 hours after the match. Significant increases in muscle soreness, CK and Mb were observed at 24 and 48 hours post-match (p<0.05). No significant changes in the 1RM strength and T test were detected during recovery (24 and 48 hours after the match). These results suggest that a basketball match induced limited muscle damage with minimal effect on performance during recovery. The small increase in muscle damage markers following a basketball match did not affect strength and agility performance.